A novel multiplex of 12 multicopy Y‐STRs for forensic application. Issue 5 (10th June 2021) - Shang, Lei; Ding, Guangshu; Mo, Xiaoting; Sun, Jing; Sun, Hui; Yu, Zhengliang; Li, Wanshui
Abstract: Y chromosomal short tandem repeats (Y‐STRs) have been applied overwhelmingly in forensic areas for solving paternity identification and sexual assault cases. Yet the widely used Y‐STR kits contain mostly single‐copy markers, which may restrict the discrimination power. Here, a novel Y‐STR multiplex was developed and validated in order to complement the currently available Y‐STR kits, especially on differentiating male relatives. The assay includes twelve multicopy Y‐STR loci (DYF371, DYF383S1, DYS385, DYF387S1, DYS389I/II, DYF399S1, DYF404S1, DYF409S1, DYF411S1, DYS464, DYS526, DYS527; four of them are rapidly mutating ones), 1 single‐copy Y‐STR (DYS391), and Amelogenin, and was optimized to amplify at annealing temperature of 59°C and 28 cycles. Validation studies show that full profiles are obtained with 0.125 ng of male DNA. The system is capable of overcoming high concentrations of inhibitors such as hematin, EDTA, and humic acid. Besides, the results demonstrate good sizing precision and the ability to detect male‐specific profiles in male/female DNA mixtures at a ratio of 1:800. Excellent species specificity was also observed in microorganisms and non‐primates, while detectable peaks were found in some primates. Based on published genetic data, gene diversity values were above 0.7 for most of the loci in our multiplex, inferring a high capacity in discriminating unrelated and related male individuals. The kit is of great potential for forensic application.